2014
DOI: 10.1186/1472-6882-14-412
|View full text |Cite
|
Sign up to set email alerts
|

Hederagenin from the leaves of ivy (Hedera helix L.) induces apoptosis in human LoVo colon cells through the mitochondrial pathway

Abstract: BackgroundColorectal cancer has become one of the leading cause of cancer morbidity and mortality throughout world. Hederagenin, a derivative of oleanolic acid isolated from the leaves of ivy (Hedera helix L.), has been shown to have potential anti-tumor activity. The study was conducted to evaluate whether hederagenin could induce apoptosis of human colon cancer LoVo cells and explore the possible mechanism.MethodsMTT assay was used for evaluating cell viability while Annexin V-FITC/PI assay and Hoechst 33342… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 40 publications
0
36
0
Order By: Relevance
“…The central event in apoptosis is the proteolytic activation of a class of cysteine aspartyl-specific proteases(Caspase) family (38,45,(50)(51)(52)(53)(54)(55). Caspases are known to act as important mediators of apoptosis and contribute to the overall apoptotic morphology by the cleavage of various cellular substrates (44,49,54).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The central event in apoptosis is the proteolytic activation of a class of cysteine aspartyl-specific proteases(Caspase) family (38,45,(50)(51)(52)(53)(54)(55). Caspases are known to act as important mediators of apoptosis and contribute to the overall apoptotic morphology by the cleavage of various cellular substrates (44,49,54).…”
Section: Discussionmentioning
confidence: 99%
“…This gene encodes a protein that belongs to a highly conserved family of cysteinyl aspartate-specific proteases that function as essential regulators of programmed cell death through apoptosis. The increase of caspase-3 expression may induce the mitochondria-dependent apoptotic pathway with the possible mitochondria-independent pathway for the caspase-8 activation for that caspase-8-mediated apoptosis induced by oxidative stress is independent of the intrinsic pathway and dependent on cathepsins (38,45,(50)(51)(52)(53)(54)(55). The intrinsic pathway of apoptosis is associated with the activation of caspase-9, which cleaves and activates caspase-3 (49)(50)(51)(52)(53)(54).…”
Section: Discussionmentioning
confidence: 99%
“…4 In recent years, HG has been observed to be biologically active, as well as many other saponins with similar structures, such as ursolic acid and corosolic acid. HG exhibits multiple pharmaceutical and biological activities, including antitumor, 2,[5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] anti-inammatory, [24][25][26][27][28][29][30] anti-depressant, [31][32][33][34][35] antineurodegenerative, [36][37][38] anti-hyperlipidemia, 4,39,40 anti-diabetic, [41][42][43] anti-leishmanial, 19,44,45 and anti-viral (against hepatitis B) activity. 46 Recently, a number of studies have investigated the use of HG as a potential anti-tumor agent.…”
Section: Introductionmentioning
confidence: 99%
“…46 Recently, a number of studies have investigated the use of HG as a potential anti-tumor agent. 5,6,[10][11][12][14][15][16] The pharmacokinetics, [47][48][49][50][51] structural modication, [17][18][19][20][21]35,38,45,46 and mechanisms of action [4][5][6][10][11][12][13][14][15][16]19,25,26,[31][32][33][34]36,37,39,40,43,45 of HG have also been studied. However, possibly owing to limited in vivo data, HG is still in the preclinical development stage.…”
Section: Introductionmentioning
confidence: 99%
“…Kittiratphatthana et al (17) reported that luteolin exerts its pro-apoptotic effect partly through generating intracellular ROS, which then contributes to the induction of mitochondria-mediated cell apoptosis. Others have indicated that the overexpression of ROS may contribute to the apoptosis through regulating B-cell lymphoma 2 (Bcl-2) family proteins, releasing cytochrome c from the mitochondria, and activating effector caspases, including caspase-3 and caspase-9 (21). Therefore, a promising strategy for the prevention and treatment of MdS has emerged via inducing apoptosis by mitochondria-mediated ROS generation.…”
Section: Introductionmentioning
confidence: 99%